Femtosecond x-ray absorption spectroscopy of pyrazine at the nitrogen K-edge: on the validity of the Lorentzian limit - Freibert, Antonia; Mendive-Tapia, David; Huse, Nils; Vendrell, Oriol (Journal of physics. B, Atomic, molecular and optical physics, 2021)
We calculate the femtosecond x-ray absorption spectrum of pyrazine at the nitrogen K-edge including the wavepacket dynamics in both the valence and core-excited state manifolds. We do not invoke the widely used short-time (or Lorentzian) approximation which neglects the nuclear dynamics after the x-ray probe excitation. Instead, we calculate the x-ray-induced polarization in the time-domain where the optical pump as well as x-ray probe pulses are explicitly described. While the non-adiabatic population transfer following the optical excitation is well reproduced in the Lorentzian limit the transient x-ray absorption spectra obtained under this approximation lack some vibronic features, even when considering the short core-hole lifetime of nitrogen. We further demonstrate the effect of an increasingly longer pulse on the observed photo-triggered wavepacket dynamics which are blurred to the point that the x-ray probe response becomes effectively time-independent.